Piloting Community Rangeland Health Workers (CRHWs) in Ethiopia: A ground-breaking innovation for One Health application in pastoral areas - Flintan, Fiona E.; Ebro, Abule (CGIAR System Organization, 2024)
HEAL and ILRI collaboration on an innovative concept of community rangeland health workers (CRHWs). Following a review of current practice and lessons learned from HEWs and CAHWs, and consultations with experts including researchers, government and community members, it was agreed that CRHWs would be supported, at least initially, to provide information and raise awareness on invasive species and noxious plants and establish a community rangeland health monitoring system. To instill opportunities for the CRHWs to be self-supporting, nurseries for growing and selling grass and tree seedlings are being established.